1993
DOI: 10.1002/jgt.3190170205
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of Hamiltonian prisms

Abstract: A characterization is established for a graph G to have a Hamilton cycle in G x K2, the prism over G. Moreover, it is shown that every 3-connected graph has a 2-connected spanning bipartite subgraph. Using this result, the existence of a Hamilton cycle in the prism over every 3-connected cubic graph is established. Further, the existence of a Hamilton cycle in the prism over a cubic 2-connected graph is also discussed. Earlier results in this direction are shown to be particular cases of the results obtained h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…In some instances, the Hamiltonicity of G guarantees that G has more than one Hamiltonian cycle [21]. There were studied in detail Hamiltonian ladders (defined by the Cartesian product G × K 2 of G and K 2 ) [22], which are a generalization of graphs of prisms.…”
Section: N) Since Permuting Rows And/or Columns Ofmentioning
confidence: 99%
“…In some instances, the Hamiltonicity of G guarantees that G has more than one Hamiltonian cycle [21]. There were studied in detail Hamiltonian ladders (defined by the Cartesian product G × K 2 of G and K 2 ) [22], which are a generalization of graphs of prisms.…”
Section: N) Since Permuting Rows And/or Columns Ofmentioning
confidence: 99%
“…By [9] (see also [1]), any 3-connected cubic graph has a hamiltonian prism. Thus, the assertion follows from Theorem 8.…”
Section: Corollarymentioning
confidence: 99%
“…For a nice survey of results on k-walks, k-trees and related topics, we refer the reader to Ellingham [4]. The prism over a graph G is the Cartesian product G2K 2 of G with the complete graph K 2 [1,7,9]. Thus, it consists of two copies of G and a 1-factor joining the corresponding vertices.…”
Section: Introductionmentioning
confidence: 99%
“…Fleischner [12] found a proof avoiding the use of the Four Color Theorem. Eventually, Paulraja [21] showed that planarity is inessential here.…”
Section: Introductionmentioning
confidence: 98%